2016
DOI: 10.1248/bpb.b16-00438
|View full text |Cite
|
Sign up to set email alerts
|

New Age Therapy for Alzheimer’s Disease by Neuronal Network Reconstruction

Abstract: Alzheimer's disease (AD) is a recognized incurable neurodegenerative disorder. Clinically prescribed medicines for AD are expected to bring about only slight symptomatic improvement or a delay of its progression. Another strategy, amyloid β (Aβ) lowing agents, has not been successful at memory improvement. We have hypothesized that an improvement in cognitive function requires the construction of neuronal networks, including neurite regeneration and synapse formation; therefore, we have been exploring candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
(86 reference statements)
0
9
0
1
Order By: Relevance
“…We hypothesized that reconstruction of damaged neuronal networks may restore neuron function, and many types of extracts and compounds have been screened for inhibition of Aβ‐induced axon and dendrite atrophy. Regrowth of axons and dendrites was found in several cases using herbal drugs and constituents . These bioactive drugs also improved memory functions in AD model mice.…”
Section: Introductionmentioning
confidence: 98%
“…We hypothesized that reconstruction of damaged neuronal networks may restore neuron function, and many types of extracts and compounds have been screened for inhibition of Aβ‐induced axon and dendrite atrophy. Regrowth of axons and dendrites was found in several cases using herbal drugs and constituents . These bioactive drugs also improved memory functions in AD model mice.…”
Section: Introductionmentioning
confidence: 98%
“…Within these neural networks, even minor mutations can cause serious diseases [4]. In the past several years, some literatures [5][6][7] have begun to explore the treatment of AD and develop drugs from the perspective of structural brain network reconstruction and neuronal circuit repair [8]. Many postmortem histological and in-vivo imaging studies indicate widespread white matter (WM) changes in patients with MCI and AD [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, drugs used for the treatment of AD only bring some degree of symptomatic relief but fail to cure or delay disease progression (Selkoe, 2011 ). Several studies with regard to inhibiting Aβ aggregation have been reported (Gervais et al, 2001 ; Bilikiewicz and Gaus, 2004 ; Aisen et al, 2006 ; Townsend et al, 2006 ; Santa-Maria et al, 2007 ; Tohda, 2016 ), but no drug has been identified that effectively blocks or reverses the process of AD progression until now. During the last decade, all phase III clinical trials including promising candidates, such as Solanezumab and Verubecestat have failed because of adverse effects and the lack of cognitive improvement (Egan et al, 2018 ; Honig et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%